Database System Development Life Cycle (DSDLC) on System Libraries for Data Manipulation Language (DML) Using SQL Server 2008: - - Didik Setiyadi (Institute of Computer Science (IOCS), 2021)
Database System Development Life Cycle (DSDCL) is a method in database development. While the database language used to modify and retrieve data in a database is Data Manilation Language (DML). The DML that is often used is Structured Query Language (SQL) which is used to search and manipulate data in relational databases. SQL consists of simple syntax in the form of commands to manipulate data, these commands are called queries. The query language is used in implementing the Library System database using SQL Server 2008 RDBMS. The first step before performing DML using the query editor, must have a database and data that has been implemented with SQL Server 2008. In this discussion, only 4 (four) DML statements are explained. namely select, insert, update and delete by using the Library System database with SQL Server 2008 RDBMS. The select statement is used to display data from a table (1 or more) in the database. Update is used to make changes to data in tables in the database. Insert is used to fill in data and delete is used to delete data in tables in the database.